Pengaruh Partisipasi dan Ketidakpastian Tugas dalam Pengembangan Sistem Informasi Manajemen Pada Kinerja Sistem Informasi (Studi Pada PTS di Lingkungan Kopertis Wilayah V-DIY) - Heru Kurnianto Tjahjono; Herland Alfa Stevany (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
Today, information systems in business even more important than a few years ago. Information technology (IT) innovations and global business environment makes the role of IT in information systems more dominant. That role of IT can enhance human resources role compete globally. Higher education institutions as places for develop human resources is required to optimize in formation systems performance. This research identified two antecedents of information systems performance. There are user participation and task uncertainty. Besides that, this research considere size of organization as moderating variable. We separate size become two proxies. University as represent high size complexity and non university as represent as low size complexity. The purpose of this research is to analyze user participation and task uncertainty as antecedents of information systems performance and consider size of organization, higher education institutions. Samples are several higher education institutions in Jogjakarta province. In general the result partially supported the hypothesis that user participation and task uncertainty are predictor of information systems performance and size of organization is considered as moderating variable partially